Gender Equality and Autonomy of Religious Communities. Recent Case Law - Meseguer, Silvia (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2025)
This paper analyzes the legal conflicts that arise when certain provisions prohibiting discrimination based on sex in civil laws conflict with the requirements arising from the protection of religious freedom and the organizational autonomy of religious denominations. The study is conducted in light of the Constitutional Court’s recent ruling, which declares that interference with the prohibition of discrimination based on gender and the right of association cannot be protected by the freedom of self-organization of religious associations. Consequently, some parameters or criteria for action are proposed that allow for a neutral and impartial judicial assessment that places the application of gender equality within religious denominations in its proper place—not only from a secular or civil perspective.
Keywords: gender equality; prohibition of gender discrimination; collective religious freedom; right of association; organizational autonomy; religious communities